The Effects of Repeated Testing, Simulated Malingering, and Traumatic Brain Injury on High-Precision Measures of Simple Visual Reaction Time - Woods, David L.; Wyma, John M.; Yund, E. William; Herron, Timothy J. (Frontiers in Human Neuroscience, 2015)
Simple reaction time (SRT), the latency to respond to a stimulus, has been widely used as a basic measure of processing speed. In the current experiments, we examined clinically-relevant properties of a new SRT test that presents visual stimuli to the left or right hemifield at varying stimulus onset asynchronies. Experiment 1 examined test-retest reliability in participants who underwent three test sessions at weekly intervals. In the first test, log-transformed (log-SRT) z-scores, corrected for the influence of age and computer-use, were well predicted by regression functions derived from a normative population of 189 control participants. Test-retest reliability of log-SRT z-scores was measured with an intraclass correlation coefficient (ICC = 0.83) and equaled or exceeded those of other SRT tests and other widely used tests of processing speed that are administered manually. No significant learning effects were observed across test sessions. Experiment 2 investigated the same participants when instructed to malinger during a fourth testing session: 94% showed abnormal log-SRT z-scores, with 83% producing log-SRT z-scores exceeding a cutoff of 3.0, a degree of abnormality never seen in full-effort conditions. Thus, a log-SRT z-score cutoff of 3.0 had a sensitivity (83%) and specificity (100%) that equaled or exceeded that of existing symptom validity tests. We argue that even expert malingerers, fully informed of the malingering-detection metric, would be unable to successfully feign impairments on the SRT test because of the precise control of SRT latencies that would be required. Experiment 3 investigated 26 patients with traumatic brain injury (TBI) tested more than one year post-injury. The 22 patients with mild TBI showed insignificantly faster SRTs than controls, but a small group of four patients with severe TBI showed slowed SRTs. Simple visual reaction time is a reliable measure of processing speed that is sensitive to the effects of malingering and traumatic brain injury.